PENINGKATAN LITERASI DIGITAL KREATIF SISWA MELALUI PEMBUATAN ANIMASI INTERAKTIF BERBASIS AI DI SMK PKP 1 JIS - Kelvin Andrean; Jiyan Suhada; Hari Setyawan (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PkM) activity is motivated by the challenges faced by Vocational High School (SMK) students in dealing with the development of Artificial Intelligence (AI) in the creative sector. The main problems identified at SMK PKP 1 JIS are competency silos between departments (DKV, RPL, and TKJ) and low efficiency in the creative pre-production phase. The aim of this activity is to increase students' Creative Digital Literacy (LDK) through an animation production workflow integrated with AI technology. The method used is Project-Based Learning (PBL) through workshops on using ChatGPT for script ideation and the Animaker platform for visual production and Text-to-Speech features. The results of the activity show a significant increase in content production efficiency and cross-disciplinary collaboration. The conclusion of this program is that the appropriate use of AI can equip students to become critical, ethical, and competitive technology users in the digital industry. Keywords: Creative Digital Literacy; Interactive Animation; Artificial Intelligence; Project-Based Learning.